Comprehensive Oncogenic Features of Coronavirus Receptors in Glioblastoma Multiforme - Chen, Anjing; Zhao, Wenguo; Li, Xiaolong; Sun, Guangyu; Ma, Zhaoyin; Peng, Lingyu; Shi, Zhongyang; Li, Xingang; Yan, Jie (Frontiers in Immunology, 2022)
The COVID-19 pandemic caused by SARS-CoV-2 infection has placed health systems under excessive pressure and especially elderly people with cancer. Glioblastoma multiforme (GBM) is a malignant brain tumor with an increasing incidence in elderly individuals, and thereby GBM patients are a vulnerable population during the COVID-19 outbreak. Accumulating studies have implied that SARS-CoV-2 might invade the brain directly via coronavirus receptors. However, little is known about SARS-CoV-2 infection in the clinical development of GBM. Here, we explored the oncogenic roles of six coronavirus receptors (ACE2, DPP4, ANPEP, AXL, TMPRSS2, and ENPEP) in GBM using bioinformatics and experimental approaches. We found that ANPEP and ENPEP were significantly increased at both the mRNA and protein levels in GBM compared with normal brain tissue. Kaplan–Meier survival curves and Cox regression analysis demonstrated that high expression of ANPEP and ENPEP is associated with poor prognosis and survival. Moreover, all receptors are positively correlated with the immune infiltration levels of monocyte. Furthermore, we identified 245 genes between COVID-19 and coronavirus receptors-correlated genes in GBM and performed a thorough analysis of their protein–protein interaction network, functional signaling pathway and molecular process. Our work explores for the first time the association of coronavirus receptors with GBM and suggests ANPEP and ENPEP as potential therapeutic targets of GBM irrespective of COVID-19.